2013
DOI: 10.1097/scs.0b013e318299777e
|View full text |Cite
|
Sign up to set email alerts
|

Early Neurodevelopment in Infants With Deformational Plagiocephaly

Abstract: The objective of this study was to characterize the early neurodevelopmental profile of Australian infants with deformational plagiocephaly (DP). Twenty-one infants with a confirmed diagnosis of DP (mean age, 7.9 months; SD, 2.0 months) were assessed on the Bayley Scales of Infant Development, Second Edition, before treatment. As a group, infants with DP showed significantly weaker motor skills compared with the normative population. Patients with DP did not significantly differ from normative population estim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…Most studies reported a male predominance, varying from 56% to 85%, but in one study females were more frequent 44 . Ten studies 27,29–33,37,42,45,46 mentioned laterality of head preference. Nine 27,30–33,37,42,45,46 of them reported a dominance to the right side (present in 53%–80%).…”
Section: Resultsmentioning
confidence: 93%
See 4 more Smart Citations
“…Most studies reported a male predominance, varying from 56% to 85%, but in one study females were more frequent 44 . Ten studies 27,29–33,37,42,45,46 mentioned laterality of head preference. Nine 27,30–33,37,42,45,46 of them reported a dominance to the right side (present in 53%–80%).…”
Section: Resultsmentioning
confidence: 93%
“…The major outcome reported for activities and participation was developmental delay. This outcome was reported in 16 papers 1,20,25–32,39,41–45 . Most studies were based on infants who had been referred to tertiary centres.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations